2019
DOI: 10.3390/nano9091281
|View full text |Cite
|
Sign up to set email alerts
|

Zingiber officinale Extract (ZOE) Incorporated with Layered Double Hydroxide Hybrid through Reconstruction to Preserve Antioxidant Activity of ZOE against Ultrasound and Microwave Irradiation

Abstract: We prepared Zingiber officinale extract (ZOE) incorporated in a layered double hydroxide (LDH) hybrid through a reconstruction method in order to preserve the antioxidant activity of ZOE from ultrasound and microwave irradiation. X-ray patterns, infrared spectroscopy, and scanning electron microscopy suggested that ZOE moieties were encapsulated in the interparticle space of reconstructed LDH, thus preserving its intact structure. Dynamic light scattering and zeta-potential measurement also supported the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…As displayed in Figure 3 a, AH-1 had irregularly shaped particles of which the size was less than 100 nm. Compared with the other three samples, AH-1 did not show clear grain boundaries, which might be attributed to the large lumps of organic moiety [ 53 , 58 , 59 ] like proteins. After calcination (AO-1), particle morphology of ruffled layers appeared along with the combustion of albumin-template ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 82%
“…As displayed in Figure 3 a, AH-1 had irregularly shaped particles of which the size was less than 100 nm. Compared with the other three samples, AH-1 did not show clear grain boundaries, which might be attributed to the large lumps of organic moiety [ 53 , 58 , 59 ] like proteins. After calcination (AO-1), particle morphology of ruffled layers appeared along with the combustion of albumin-template ( Figure 3 b).…”
Section: Resultsmentioning
confidence: 82%
“…As indicated in the open circle curve in Figure 3 A, the average zeta potential of MTX-LDH at neutral pH was 4.61 ± 0.97 mV, showing almost neutral surface charge. Generally, the zeta potential of LDH at neutral pH is very positive, ~+30 mV [ 3 , 55 , 56 , 57 , 58 ], due to the strong positive charge density of LDH layers. However, the zeta potential drops to the neutral value region due to the MTX moieties, which were mostly intercalated into LDH but partially covered the outer surface of LDH layers [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…An et al found that microwave drying of Zingiber officinale rhizome resulted in a decrease in TPC and had almost no effect on antioxidant potential compared to fresh ginger extract (DPPH, FRAP, ABTS tests) [103]. On the other hand, Kim et al, studying the effect of microwave radiation on the antioxidant activity of ginger rhizome extract, noticed a negative effect of this type of treatment (DPPH test) [104]. Interestingly, these results are opposite to the results obtained in the current study for the Alpinia rhizome, which revealed that subjecting the rhizome to microwave processing (regardless of the processing time) had a significant positive effect on TPC and antioxidant activity measured using DPPH assay.…”
Section: Discussionmentioning
confidence: 99%